Formal Aspects in Security and Trust Third International Workshop, FAST 2005, Newcastle upon Tyne, UK, July 18-19, 2005, Revised Selected Papers - Dimitrakos, Theo; Martinelli, Fabio; Ryan, Peter Y.A; Schneider, Steve (Security and Cryptology ;, 2006)
This book constitutes the thoroughly refereed post-proceedings of the Third International Workshop on Formal Aspects in Security and Trust, FAST 2005, held in Newcastle upon Tyne, UK in July 2005. The 17 revised papers presented together with the extended abstract of 1 invited paper were carefully reviewed and selected from 37 submissions. The papers focus on formal aspects in security and trust policy models, security protocol design and analysis, formal models of trust and reputation, logics for security and trust, distributed trust management systems, trust-based reasoning, digital assets protection, data protection, privacy and ID issues, information flow analysis, language-based security, security and trust aspects in ubiquitous computing, validation/analysis tools, web service security/trust/privacy, GRID security, security risk assessment, and case studies.